Camp for organizing committee and programme handling (COACH) 2025 - Azari, Nur Aqilah Najihah; Zamery, Muhammad ‘Izzuddin; Jahidin, Aisyah Hasyila (Faculty of Pharmacy, 2025)
On Saturday, 19 April, the Society of Pharmacy Students (SOPHYS) and Sekretariat Mahasiswa Fakulti Farmasi (SMF) successfully hosted COACH 2025: Camp for Organising Committee and Programme Handling. The camp was designed to equip newly appointed committee members with essential leadership, problem-solving and teamwork skills, whilst also strengthening their ability to communicate effectively and plan events, which are key ingredients for effective student governance.